The Offshore Group of Banking Supervisors as a Mechanism of International Legal Regulation of Financial Offshore Centers - A. Kh. Aslanov (Московский журнал международного права, 2010)
This article discusses the conditions of membership and participation in The Offshore Group of Banking Supervisors (OGBS), its activities and objectives, as well as cooperation in international initiatives in the area of legal regulation of offshore financial centers.